The means, the pretext and the intercession - Alkinani, Hanan Jasib (Al-Adab Journal, 2018)
Prayer and peace be upon Muhammad and his home good his companions. The most important reached the researcher through the search :the subject of means , pretext and intercession is one of the most important subject in our lives , through which we obtain intercession in the world and the hereafter .the research includes two topics , the first means ,the pretext , the intercession , the difference between them , and the view of the jurists on the issne , and the second topic inchndes the intercession , legimacy and judgment of the fuqaha.the meas is the closest to the slave to god almighty , but the pretext is the way to reach the person to the object and intercession is to pray to get to the thing.the legitimacy and evidence of intercession and al-ousayla are many cited by the researcher in the research folds .At the conclusion of the research , we ask god almighty to resolve the intercession of the prophet Muhammad and the pure goodness of the prophet . and peace and blessings be upon our master Muhammad and his diving good and the owners good guys almentajabin .